2012
DOI: 10.1001/archfacial.2012.662
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Scalp and Forehead Defects Using External Tissue Expander

Abstract: External tissue expansion is a safe and effective technique for closing large scalp and forehead defects that would otherwise require skin grafting or free flap reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…As detailed in the Head and Neck, Including Scalp section, a prospective case series included seven cases using DermaClose for scalp wounds. 35 Primary closure was achieved in five of seven patients. One patient with poorly controlled diabetes, who previously underwent external beam radiation, experienced partial skin loss and required bilateral advancement rotational flaps.…”
Section: Diabetic Foot Woundsmentioning
confidence: 94%
See 1 more Smart Citation
“…As detailed in the Head and Neck, Including Scalp section, a prospective case series included seven cases using DermaClose for scalp wounds. 35 Primary closure was achieved in five of seven patients. One patient with poorly controlled diabetes, who previously underwent external beam radiation, experienced partial skin loss and required bilateral advancement rotational flaps.…”
Section: Diabetic Foot Woundsmentioning
confidence: 94%
“…35 Tissue expansion allows replacement with like-for-like tissue, potentially improving cosmetic appearance compared with other techniques. 35 Clinical evidence. A retrospective, singlecenter study of six patients underwent definitive cranioplasty with preoperative CETE reported an average 16% increase in scalp surface area (range, 6.6-35.0%), resulting in all patients having adequate tissue for tension-free closure.…”
Section: Head and Neck Including Scalpmentioning
confidence: 99%
“…These devices come in the form of adhesive and elastic tapes 44,45 or a mechanical tensioning device. 46 Both of these devices are applied for 1-14 days depending on the defect or surgical goal. As such, the principle benefit is derived from mechanical creep as described previously as there is not enough time for the physiological changes seen in prolonged expansion to occur.…”
Section: External Tissue Expansionmentioning
confidence: 99%
“…The external adhesive devices (DynaClose; Canica Design Inc.) have proven useful in the primary closure of forearm free flap donor sites when applied to the donor site 1 week prior to flap harvest. 44,45 The external tensioning device (Derma Close RC; Wound Care Technologies Inc.) has proven useful in the management of large scalp defects with reduction in wound size from 50 to 99% after 6 to 14 days of external expansion 46 (Fig. 50.3).…”
Section: External Tissue Expansionmentioning
confidence: 99%
“…Some case series with promising results have been reported in the literature. 61,62 However, further clinical experience is warranted before widespread use of these novel devices.…”
mentioning
confidence: 99%